2003
DOI: 10.5144/0256-4947.2003.223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramadan Fasting on Clinical and Biochemical Parameters in Healthy Adults

Abstract: Coronary heart disease (CHD) is primarily a disease of occidental culture, being more prevalent in populations that have adopted a high-fat, high-cholesterol diet, who smoke and do not engage in sufficient physical activity. 1 The Islamic religion prescribes fasting during Ramadan for all healthy Muslims for ostensibly moral and spiritual reasons. It may, however, be viewed as an effective model for CHD risk profile modulation.The effect of Ramadan fasting on cardiovascular risk factors is still a matter of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 24 publications
9
68
1
2
Order By: Relevance
“…Mean weight was reduced slightly in Ramadan in this study. A majority of studies showed a significant decrease in mean weight in Ramadan (16,18,(20)(21)(22)(23)(24) but this was recouped in Shawwal (21,23). Shruthi et al indicated that the decrease in weight during Ramadan could be due to a reduction in fluid intake and a decline in glycogen-bound water stores (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean weight was reduced slightly in Ramadan in this study. A majority of studies showed a significant decrease in mean weight in Ramadan (16,18,(20)(21)(22)(23)(24) but this was recouped in Shawwal (21,23). Shruthi et al indicated that the decrease in weight during Ramadan could be due to a reduction in fluid intake and a decline in glycogen-bound water stores (24).…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were: pregnancy, those diagnosed with renal failure, hepatic impairment, diabetes mellitus, hypertension, hyperlipidaemia, thyroid problems or cardiovascular diseases and users of weight reducing agents. The participants were requested to visit the project office 3 times: in the last 10 days of Shaban (the month before Ramadan), [22][23][24][25][26][27][28][29][30] July2011; in the last 10 days of Ramadan, 20-29 August 2011; and in the last 10 days of Shawwal (the month after Ramadan), 19-27 September 2011, for blood pressure and anthropometric measurements and an interview for a questionnaire. The blood samples were collected during the morning after 12 hours fasting in Shaban and Shawwal and about 12 hours after sahure (morning meal) in Ramadan at the collection points of the pathology laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average BMI reduction in obese patients was 0.9 kg/ m 2 (18). Also, Fakhrzadeh et al found that fasting caused a significant reduction in weight and BMI in men and in waist circumference in women (19). In contrary, a study from Saudi Arabia reported weight gain during Ramadan, while others did not find any significant change in body weight (20).…”
Section: Body Weight and Body Mass Indexmentioning
confidence: 71%
“…Certain authors have found a significant decrease in TC and LDL-C during Ramadan, Greek Orthodox fasting and Daniel fasting. 13,14,20,31,32 In scientific literature, results are conflicting for triglycerides and HDL-C. 13,14,17,20,33 LDL / HDL and TC / HDL ratio decreased significantly at the end of the study.…”
Section: Discussionmentioning
confidence: 98%